Determinan Kinerja Sistim Informasi Akuntansi dimoderasi oleh Pendidikan dan Pelatihan - Pattiasina, Victor; Noch, Muhamad Yamin; -, Saling; Bonsapia, Melyanus; Patiran, Andarias (Lembaga Penelitian & Pengabdian Masyarakat (LPPM) STIA Said Perintah, 2021)
This study examines the determinants of accounting information system performance (a study at PT. PLN Persero, customer service unit, Jayapura district). Testing was carried out on a sample of 71 respondents. The sample method used was purposive sampling. data collection was carried out by direct survey. Hypothesis testing is tested empirically using moderated regression. The results show that the technical ability of personnel has no effect on the performance of the accounting information system at PT. PLN Persero Pelanggal Service Unit Kab. Jayapura, user involvement affects the performance of the accounting information system on the performance of the accounting information system at PT. PLN Persero Pelanggal Service Unit Kab. Jayapura, the sophistication of personnel technology affects the performance of the accounting information system. The performance of the accounting information system at PT. PLN Persero Pelanggal Service Unit Kab. Jayapura, training and education moderate the technical capabilities of personnel on the performance of the accounting information system at PT. PLN Persero Pelanggal Service Unit Kab. Jayapura, training and education moderate user involvement on the performance of the accounting information system at PT. PLN Persero Pelanggal Service Unit Kab. Jayapura and the last training and education moderate the technological sophistication of personnel on the performance of the accounting information system at PT. PLN Persero Pelanggal Service Unit Kab. Jayapura Keywords: Performance of Accounting Information Systems, Education and Training.